Perlindungan Hukum Terhadap Kerusakan Benda Cagar Budaya Di Aceh Utara - Nasir, Muhammad; Harun, Harun; Ayun, Siti Qurrata (Fakultas Hukum Universitas Malikussaleh, 2023)
Cultural Heritage in North Aceh suffered destruction both intentionally and unintentionally. Its existence must be maintained to survive and avoid various threats that can speed up the weathering process. The management of cultural heritage problems is often neglected, this is because the people of Aceh do not understand the problem of cultural heritage. With the existence of legal protection, it is hoped that it will be able to preserve cultural heritage objects. The Aceh region has special autonomy and has Law No. 11 of 2006 concerning the Government of Aceh (UUPA). It is explained in article 149 that: